Presentation Basics - Rosania, Robert (Association for Talent Development, 2003)
Presentation Basics is designed to provide the basic training tools to individuals and organizations facing the reality of rapidly changing jobs, roles, and, responsibilities. This book offers a simple, step-by-step approach that guides readers through the entire process from preparation, to creating the right environment, to recovery when things go wrong in a presentation.